A guide to the Revelation - Van Daalen, David H. (London SPCK, 1986)
This guide features a brief survey of the historical and literary background to the Revelation and John's purpose in writing it. Fuller notes on some general themes support the detailed interpretation. The question material includes subjects for discussion.
Keywords: Bible. -- Revelation -- Commentaries. Bible. -- Revelation. Bible -- N.T -- Revelation - Commentaries